LincROR Mediates the Suppressive Effects of Curcumin on Hepatocellular Carcinoma Through Inactivating Wnt/β-Catenin Signaling - Shao, Jiang; Shi, Chuan-Jian; Li, Yun; Zhang, Feng-wei; Pan, Fei-fei; Fu, Wei-ming; Zhang, Jin-fang (Frontiers in Pharmacology, 2020)
As one of the leading causes of cancer-related death in the world, hepatocellular carcinoma (HCC) has continued to attract growing attention in recent decades. The use of traditional Chinese herbs in medicine has been practiced for thousands of years, and holds the potential of being a possible treatment for HCC. Curcumin, a bioactive ingredient derived from Curcuma longa, exhibits anti-tumor activity in various cancers. Although the effects of Curcumin on HCC have been elucidated, the underlying mechanism remains unclear. In the present study, Curcumin was demonstrated to inhibit the proliferation of HCC cells via inducing cell cycle arrest and apoptosis. Several previously reported lncRNAs related to tumorigenesis were chosen for examination of their expression profiles, and lincROR was found to be the most down-regulated in the Curcumin-treated HCC cells. Furthermore, Curcumin was found to decrease β-catenin expression and induce the inactivation of Wnt/β-catenin signaling. Therefore, Curcumin suppressed tumor growth through a lincROR/β-catenin regulatory pattern. In conclusion, our results demonstrated that Curcumin suppressed the cell proliferation via the down-regulation of lincROR and inactivation of Wnt/β-catenin signaling, suggesting that it may be a potential anti-cancer candidate for HCC patients with activated Wnt/β-catenin signaling.